2019
DOI: 10.1186/s13046-019-1440-4
|View full text |Cite
|
Sign up to set email alerts
|

Prohibitin (PHB) expression is associated with aggressiveness in DLBCL and flavagline-mediated inhibition of cytoplasmic PHB functions induces anti-tumor effects

Abstract: BackgroundDiffuse large B-cell lymphomas (DLBCLs) are aggressive lymphomas accounting for approximately a third of non-Hodgkin lymphomas. Prohibitin 1 (PHB1) and prohibitin 2 (PHB2) are scaffold proteins that promote mitochondria homeostasis and consequently cell survival, but biological functions of cytoplasmic PHBs remain largely unknown in DLBCL.MethodsPHB expression was analyzed in 82 DLBCL biopsies and five DLBCL cell lines by immunohistochemistry (IHC) and Western blotting. Pharmacological inhibition of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(39 citation statements)
references
References 55 publications
1
36
0
Order By: Relevance
“…Very likely, PHB2 and other prohibitins will represent the topics of specific interest in next future as further details in PHB2 biology will contribute to gain insights into unexplored mitophagy mechanisms and virus infections. A further exciting research area will be to highlight PHB2 as an important target which may be useful in diagnosis and therapy of PHB-dependent diseases, including viral diseases [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very likely, PHB2 and other prohibitins will represent the topics of specific interest in next future as further details in PHB2 biology will contribute to gain insights into unexplored mitophagy mechanisms and virus infections. A further exciting research area will be to highlight PHB2 as an important target which may be useful in diagnosis and therapy of PHB-dependent diseases, including viral diseases [ 15 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it has been suggested that PHB2 is required for cholestasis-induced mitophagy, wherein PHB2 recruits LC3 to the damaged mitochondria via interaction with p62/SQSTM1 and LC3 [ 16 ]. Recently, PHB2 overexpression has been shown to be associated with aggressiveness in diffuse large B-cell lymphomas and targeting PHBs may have a therapeutic potential, notably in the aggressive subtypes [ 17 ]. PHBs are believed to be play a crucial a role in the pathogenesis of virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…In human hematopoietic tissue tumors, overexpression of PHB is detected in the mitochondria, and PHB improves cell survival under oxygen stress [22]. Cytoplasmic PHB expression levels in diffuse large B-cell lymphoma cells are positively associated with serum LDH, PHB2, and Ki-67 expression, and tend to be inversely linked to event-free survival [12]. Our results revealed that the cytoplasmic PHB expression levels of nasal ENKTCL cells are inversely correlated to OS.…”
Section: Discussionmentioning
confidence: 76%
“…In the nucleus, PHB controls the cell cycle, cell proliferation, and cell apoptosis by interacting with cell cycle-regulated proteins, transcription factors, and apoptosis-associated proteins [8][9][10]. The abnormal expression of PHB is closely associated with the development and progression of a number of human cancers [11][12][13][14]. The role of PHB in the development of nasal ENKTCL remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MNK inhibition by FL3, a synthetic flavagine and ligand of PHBs, determined antitumor activities in vitro and in vivo by inhibiting MNK-dependent eIF4E phosphorylation. This MNK1 inhibition reduced Bcl-2 and c-Myc expression, inducing apoptosis that would allow the treatment of rituximab resistant diseases [109].…”
Section: Mnk In Hematological Cancersmentioning
confidence: 97%